MIGRAINE PRODROMAL FEATURES IN ABDOMINALLY OBESE PATIENTS - Nikiforova, O.S.; Delva, M.Yu. (World of Medicine and Biology, 2019)
Nowadays, it has been found that abdominal obesity (AO) can modify migraine clinical course. The purpose of the work was to study and to assess migraine prodrome characteristics in abdominally obese patients with episodic and chronic migraine. There were 96 episodic and chronic migraineurs examined with normal body weight and AO. Data were collected using structured questionnaires. In 76 cases (78.5%) migraine prodrome had been reported. Abdominally obese patients compared to normal body weight migraineurs had a higher rate of prodromal symptoms (83% vs. 75%) and experienced statistically higher mean number of prodromal symptoms per patient (4.0 (4.0-6.0) vs 6.0 (5.4-7.0). p
Keywords: migraine; prodrome; abdominal obesity